Changes in adipose tissue and biochemical parameters after aerobic exercise in overweight and obese women - Sertbaş, Meltem; Elarslan, Serkan; Şenocak, Emre (Journal of Surgery and Medicine, 2021)
Background/Aim: Obesity is a global epidemic, and it is more common in women due to physiological differences. Exercise programs are the cornerstones of obesity treatment. This retrospective study aimed to examine the effect of moderate-intensity continuous aerobic exercise (MICT) program on body composition, biochemical parameters, and cardiovascular risk in overweight and obese female. Methods: This retrospective cohort study analyzed the data of overweight and obese women who exercised for 12 weeks. The exercise program was maintained under the supervision of a physiotherapist three non-consecutive days a week. Each session was performed for 60 minutes at an intensity of 50% to 65% of maximum heart rate (HRmax). Body composition was evaluated by TANITA bioelectrical impedance analysis system, and aerobic capacity was assessed with 6-minute Walking Test (6-MWT). Biochemical parameters were analyzed in the laboratory. All results of the participants were obtained from the patient files. Results: Body Mass Index (BMI), Fat Mass (FM-kg), Fat-free Mass (FFM-kg), Total Body Water (TBW-kg), and aerobic capacity improved after the implementation of the exercise program (P<0.05 for all). There was no significant change in blood parameters except HDL (P=0.002). An 11% reduction was observed in cardiometabolic risk factors due to the increased HDL. Conclusion: The MICT program appears suitable for improving body composition and aerobic capacity with 50-65% intensity for 12 weeks. However, we think that exercise intensity should be increased for more biochemical benefits.